THE STUDENTS’ SPEAKING ABILITY WITH (ICARE) MODEL - Junaid Junaid (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2017)
The research aimed at finding out the improvement of students’ speaking ability by using Introduction, Connection, Application, Reflection, Extend (ICARE) Model at Class VIII.B in MTs. Muallimin Muhammadiyah Makassar. The method of this research was Classroom Action Research that consisted of two cycles. One cycle consisted of four meeting. It means that there were eight meeting in two cycles. This classroom action research was done at MTs. Muallimin Muhammadiyah Makassar for English subject. As subject in this research was Class VIII.B in Junior High School in 2012-2013 Academic Years with student’s number as about 29 students. Those consist of 29 women. Instruments are speaking test and observation sheet. The findings of this research were the improvement of the students’ speaking ability in terms of speaking accuracy and speaking fluency in which the mean score of diagnostic test was 5.17, the mean score of cycle I was 6.06 and the mean score of cycle II was 7.21. The result above indicated that there was significant improvement of the students’ speaking ability in terms of speaking accuracy and speaking fluency in the application of form Introductioon, Connection, Application, Reflection, Extend (ICARE) Model at class VIII.B in MTs. Muallimin Muhammadiyah Makassar.